Train the (women) trainers beekeeping - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Train the (women) trainers beekeeping A Midweek course designed for women who are trainee of extension workers and farmers, and who have some experience in bee-handling, is on offer from the Agricultural Education and Training Unit of Wolverhampton...